ელექტრონული მიმოწერა და თავაზიანობა /სტუდენტებისა და ფაკულტეტის ელექტრონული კომუნიკაცია/ - გოგალაძე, ეკატერინე (My University, 2021)
Our century is characterised by the rapid development of innovations and technologies. People, human daily life, human relationships, types and means of communication have changed rapidly. The human of the modern world is constantly receiving a stream of new information, he is constantly in the space of communication, rethinking the received information, his brain responds with amazing speed to the current changes that are instantly changing and transforming. With everything, the communication area has changed: it expanded and took on a global look. The means of establishing communication (mobile/E-mail connection, internet connection) have been greatly simplified and diversified. The latest technological advances in communication tools have made it possible to establish a fast connection with any point on the earth. Electronic correspondence has become one of the main sources of communication in modern life. And in the last few years, electronic communications, in the face of a pandemic caused by the spread of the COVID virus, have virtually replaced direct contacts. All accredited universities in Georgia have switched to an online teaching format. The university administration has also moved to an online format. Students communicate remotely with the relevant departments through e-mail correspondence with various requests to the administrative departments. The study aims to analyze the electronic correspondence of students and university administrative and academic staff with a view to the concept of courtesy. Because the students’ letters mainly included the requests, the main issue of the research was the request as one of the etiquette situations. For the study, there was selected student correspondences with TSU administrative departments in the 2019-2021 academic year were selected. Altogether, 200 e-mails of Georgian-speaking and non-Georgian speaking students were selected chosen. The data were processed by quantitative research method, and the results are presented in the form of tables. In this paper, we briefly discuss theories about the concept of politeness (Brown & Levinson; Goff man; Leech), which is a theoretical framework for research. The results of the study allowed us to rethink the essence of politeness.
E-MAIL COMMUNICATION AND POLITENESS /E-MAIL COMMUNICATION BETWEEN STUDENTS AND FACULTY MEMBERS/
კონფერენცია მიძღვნილია აკადემიკოს კოტე წერეთლის 100 წლის იუბილესადმი/ DEDICATED TO THE 100TH ANNIVERSARY OF ACADEMICIAN KONSTANTINE TSERETELI
Keywords: კომუნიკაცია; ელექტრონული კომუნიკაცია; თავაზიანობა; სამეტყველო აქტები; თხოვნა; Communication; E-mail communication; politeness; speech acts; request